IL-6 -G174C PROMOTER GENE POLYMORPHISM, METABOLIC RISK MARKERS AND HYPERANDROGENEMIA IN POLYCYSTIC OVARIAN SYNDROME - GUPTA VANI; GUPTA VANDANA; KUMAR SANDEEP; SRIVASTAVA NIDHI; PRADEEP YASHODHARA (International Journal of Pharma and Bio Sciences, 2013)
The present study was aimed to assess the IL-6 G174C gene polymorphism, metabolic risk markers, hyperandrogenemia and Insulin Resistance in PCOS women. Total 439 women were enrolled. Circulating IL-6, Insulin, lipid profile, hyperandrogenemic parameters were measured in the groups and subgroups, insulin resistance was calculated and IL-6- G174C genotyping was done. The observation shows significantly high frequency distribution of mutant genotype CC+GC (p=<0.001; OR=2.76, 95%CI=1.69-4.49) and mutant C allele (p=<0.001, OR=1.75, 95%CI=1.34-2.28) in PCOS women compared to non-PCOS group and in metabolic subgroups compared to non metabolic subgroups. In conclusion, the mutant C allele and mutant genotype of IL-6 promoter gene polymorphism were significantly associated with PCOS, high circulatory IL-6 and metabolic risk markers irrespective of presence or absence of PCOS. Women having mutant genotype of IL-6 gene and high circulatory IL-6, central obesity, Insulin resistance and dyslipidemia are more prone for development of cardio metabolic diseases.